Characteristics of the front-line child welfare workforce. (June 2018) - Edwards, Frank; Wildeman, Christopher
Abstract: In this study, we provide new national- and state-level estimates of workload and workforce instability among child welfare agencies using previously unavailable data that includes unique identifiers for US child welfare caseworkers in 46 states and supervisors in 43 states. We identify and describe 139, 921 unique caseworkers and 31, 124 unique supervisors who were in the child welfare workforce between 2003 and 2015. The median caseworker handles 55 cases annually and is on the job for about 1.8 years. The median state has an annual front-line caseworker turnover rate of between 14 and 22% annually, and a supervisor turnover rate of about 20% annually. Highlights: We provide new nationally comparable data on the characteristics of the child welfare workforce. Median national turnover is between 14 and 22% of caseworkers per year. The median caseworker has an active caseload for 1.8 years before exiting the front-line workforce. The median caseworker handles 55 cases per year. The median supervisor handles 88 cases per year. Workforce characteristics vary dramatically across the states.